2015
DOI: 10.1016/j.aorn.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture and Care: A Program to Prevent Surgical Errors

Abstract: Surgical errors are under scrutiny in health care as part of ensuring a culture of safety in which patients receive quality care. Hospitals use safety measures to compare their performance against industry benchmarks. To understand patient safety issues, health care providers must have processes in place to analyze and evaluate the quality of the care they provide. At one facility, efforts made to improve its quality and safety led to the development of a robust safety program with resources devoted to enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…The highest number of reported good catches occurred in the second month of the project, possibly after staff members realized that the project team took action to improve the issues identified in the first month. In similar studies, staff members have reported that lack of action or feedback about actions taken was a deterrent to reporting . Compared with the year before the project in which personnel completed 85 electronic risk management reports, all of which came from the preoperative area and 83 (98%) of which were related to procedure cancellation, after project implementation, OR personnel reported most good catches (66%, n = 258) with many of the reported problems stemming from the sterile processing department.…”
Section: Discussionmentioning
confidence: 99%
“…The highest number of reported good catches occurred in the second month of the project, possibly after staff members realized that the project team took action to improve the issues identified in the first month. In similar studies, staff members have reported that lack of action or feedback about actions taken was a deterrent to reporting . Compared with the year before the project in which personnel completed 85 electronic risk management reports, all of which came from the preoperative area and 83 (98%) of which were related to procedure cancellation, after project implementation, OR personnel reported most good catches (66%, n = 258) with many of the reported problems stemming from the sterile processing department.…”
Section: Discussionmentioning
confidence: 99%
“…Education around the importance of speaking up and challenging authority is essential; however, unless supported by accessible reporting systems and transparency of organisations, education on its own will not be enough. 42,44 A transformation in culture regarding hierarchy will be required, which is arguably the most important modifiable factor. Future research could consider the effect of a change in the undergraduate curriculum to try and address the lack of education around speaking up.…”
Section: Discussionmentioning
confidence: 99%
“…42 This contrasts with a Massachusetts General Hospital initiative which was undertaken to improve the quality and safety program, particularly in the perioperative department. 44 A survey showed that 44% of staff did not feel able to speak up if they felt something was wrong, but felt they would do so 'knowing I have the support of management and my peers' and 'engaging in a conversation with all parties involved in the incident'. To this end, the development of an electronic safety reporting system, and formal debriefings and feedback after adverse events was initiated.…”
Section: Do Qualitatively Identified Barriers Have a Significant Effementioning
confidence: 99%
“…There continues to be a greater emphasis on a culture of safety in health care and team members are encouraged to speak up if they have concerns about patient safety. Similar results from recent studies support the main theme of the environment as a major cause of errors in which distractions, communication, and being rushed appear as variables . Researchers identified distractions (eg, loud music, cell phones) as posing a threat to patient safety, consistent with findings from our study …”
Section: Discussionmentioning
confidence: 99%